(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This paper examines the historical rise of Amir Temur as a major political and military figure whose influence extended far beyond Central Asia. It analyzes the strategic, political, and ideological foundations that enabled him to transform a fragmented regional power structure into a centralized empire with significant impact on Eurasian geopolitics. The study also evaluates how Temur’s leadership, military innovations, and state-building policies positioned him as a global actor of the late medieval period. Rather than treating his rise as inevitable or purely heroic, this paper critically assesses the structural conditions and strategic choices that shaped his emergence.